KONTRIBUSI POWER OTOT TUNGKAI DENGAN KETEPATAN SERVIS BOLA VOLI PADA CLUB PUTRA SMP NEGERI 7 PEKANBARU - Oci Robain; Slamet Slamet; Agus Sulastio (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This study aims to determine the Contribution of Leg Muscle Power with the Accuracy of Volleyball Service at the men’s club in Junior High School 7 Pekanbaru. This research was conducted using a correlational research design. In this study the population used was the men’s club Junior High School 7 in Pekanbaru, totaling 18 people. The sample in this study were all students at the men's club in junior high school 7 in Pekanbaru, totaling 18 people. Correlation analysis technique used is Product moment correlation. From the calculation results it is known t count = 2.21 while t table = 1.746 so t count = 2.21> t table = 1.746. A conclusion can be drawn, namely: There is a significant relationship between of the Leg Muscle Power with Accuracy of Volleyball Service at the Junior High School 7 Pekanbaru. So that the contribution value is obtained KD = 0.4832 x 100% = 23.33%. and can be concluded : there is a contribution between leg muscle power and the accuracy of volleyball service at the men’s club in Junior High School 7 Pekanbaru.Key Words: Leg Muscle Power, Service Accuracy, Volleyball, Contribution